2016
DOI: 10.1080/17425247.2016.1208650
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles for imaging and treatment of metastatic breast cancer

Abstract: Introduction Metastatic breast cancer is one of the most devastating cancers that have no cure. Many therapeutic and diagnostic strategies have been extensively studied in the past decade. Among these strategies, cancer nanotechnology has emerged as a promising strategy in preclinical studies by enabling early identification of primary tumors and metastases, and by effective killing of cancer cells. Areas covered This review covers the recent progress made in targeting and imaging of metastatic breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 102 publications
(144 reference statements)
1
57
0
Order By: Relevance
“…Nanoparticle-based approaches are distinctly attractive for breast cancer therapy, diagnosis and drug delivery owing to their tiny size, capability of surface modication using a variety of small ligands and biomacromolecules, and ability to accumulate into tumors owing to the enhanced permeability and retention effect. 4,5 The employment of nanocarriers as drug delivery is a key strategy for treatment of cancers. Several types of nano-systems have been extensively investigated for chemotherapy delivery on a more effective and less toxic fashion, including polymers, liposomes, dendrimers, solid lipid and inorganic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticle-based approaches are distinctly attractive for breast cancer therapy, diagnosis and drug delivery owing to their tiny size, capability of surface modication using a variety of small ligands and biomacromolecules, and ability to accumulate into tumors owing to the enhanced permeability and retention effect. 4,5 The employment of nanocarriers as drug delivery is a key strategy for treatment of cancers. Several types of nano-systems have been extensively investigated for chemotherapy delivery on a more effective and less toxic fashion, including polymers, liposomes, dendrimers, solid lipid and inorganic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles offer an option for photothermal therapy and magnetothermal therapy. They can also be used as a contrast enhancement agent for image-guided radiotherapy [ 218 ]. Gastric cancer is the second most malignant tumour in the world.…”
Section: Theranosticsmentioning
confidence: 99%
“…A significant proportion of deaths result from cancer metastases [124]. Several studies have suggested that early metastatic cancer cells can be targeted with NPs [125,126], although the targeting of metastatic cancers with nano-objects, which have a relatively small size and low vascularization, has proven to be a Herculean task. To achieve this goal, Peiris et al fabricated chain-shaped NPs with c(RGDfC) conjugated on their surfaces for tumoral vascular targeting [3].…”
Section: Fabrication Of Integrin-targeted Nps For Cancer Diagnosismentioning
confidence: 99%